Modelling of Electromagnetic Scattering by a Hypersonic Cone-Like Body in Near Space - Ji-Wei Qian; Hai-Li Zhang; Ming-Yao Xia (International Journal of Antennas and Propagation)
A numerical procedure for analysis of electromagnetic scattering by a hypersonic cone-like body flying in the near space is presented. First, the fluid dynamics equation is numerically solved to obtain the electron density, colliding frequency, and the air temperature around the body. They are used to calculate the complex relative dielectric constants of the plasma sheath. Then the volume-surface integral equation method is adopted to analyze the scattering properties of the body plus the plasma sheath. The Backscattering Radar Cross-Sections (BRCS) for the body flying at different speeds, attack angles, and elevations are examined. Numerical results show that the BRCS at a frequency higher than 300 MHz is only slightly affected if the speed is smaller than 7 Mach. The BRCS at 1 GHz would be significantly reduced if the speed is greater than 7 Mach and is continuously increased, which can be attributed to the absorption by the lossy plasma sheath. Typically, the BRCS is influenced by 5~10 dBm for a change of attack angle within 0~15 degrees, or for a change of elevation within 30~70 km above the ground.